1995
DOI: 10.1080/00223980.1995.9914966
|View full text |Cite
|
Sign up to set email alerts
|

Can Accurate Knowledge Reduce Wishful Thinking in Voters' Predictions of Election Outcomes?

Abstract: About 3,000 Israeli voters were asked to predict the outcomes of the 1992 general election and to state their political preference. Political science students were found to possess more accurate knowledge than education students about some outcomes of the previous (1 988) election, but the predictions made by both groups varied as a function of their preferences, indicating a wishful thinking effect. Wishful thinking effects of the same magnitude were found for groups differing in the accuracy of their knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 9 publications
2
36
1
Order By: Relevance
“…There is also ample evidence from psychology that desires exert a powerful influence on beliefs, a phenomenon that psychologists call "motivated reasoning" (Kruglanski 1996;Babad 1995;Babad and Katz 1991;Kunda 1990). Economists, too, have been interested in motivated formation of beliefs, but have focused more on modeling the phenomenon than on studying it empirically.…”
Section: Related Literaturementioning
confidence: 96%
“…There is also ample evidence from psychology that desires exert a powerful influence on beliefs, a phenomenon that psychologists call "motivated reasoning" (Kruglanski 1996;Babad 1995;Babad and Katz 1991;Kunda 1990). Economists, too, have been interested in motivated formation of beliefs, but have focused more on modeling the phenomenon than on studying it empirically.…”
Section: Related Literaturementioning
confidence: 96%
“…However, the investigation of the role of knowledge in attenuating the effect of wishful thinking has yielded mixed results. Whereas Granberg and Brent (1983) found that in US presidential elections wishful thinking was strongest among poorly informed citizens, Babad (1995) was unable to support this finding in his study of the 1992 Israeli election.…”
Section: Economic Perceptions In Central and Eastern Europementioning
confidence: 89%
“…Dolan and Holbrook (2001) have aptly described the debate about the sources of public opinion as the role of affect versus cognition in the formation of perceptions. In the absence of cognitive resources, but arguably even when such resources are present (Kahneman et al 1982;Babad 1995), individuals tend to resort to emotion, affect, and predispositions to help them form judgments (Lavine et al 2005). As a general rule, people tend to fit their perceptions of reality into their preexisting picture of the world or a set of longstanding preferences (Dolan and Holbrook 2001), thus achieving cognitive consistency (Festinger 1957).…”
Section: Economic Perceptions In Central and Eastern Europementioning
confidence: 99%
See 2 more Smart Citations